Parental knowledge and practice on childhood caries prevention in northern Vietnam - Vu, Dung Anh; Vu, Hai Minh; Vu, Hoang Minh; Tran, Phuc Thai; Duong, Hoang Huy; Tran, Kham Quoc; Nguyen, Bach Xuan; Luong, Hien Xuan (Frontiers in Public Health, 2023)
This study was conducted to describe the knowledge and practices on dental caries prevention among parents of preschool children in Vietnam and identify associated factors. A cross-sectional study was conducted in three preschools in Northern Vietnam in 2020. A total of 316 parents of preschool children were randomly recruited. Knowledge and practices regarding early dental caries prevention were asked by using a structured questionnaire. Multivariate Tobit regression was used to examine factors associated with knowledge and practice scores. Results showed four aspects of knowledge that had the lowest proportion of parents having correct responses included timing of complete primary tooth replacement (12.3%), benefits of undergoing regular dental examination (31.7%), technique for brushing a child's teeth (33.9%), and duration for brushing (36.7%). The knowledge of parents was moderately low at 6.3/12 (SD=2.3). The practices of parents were moderately good with the mean practice score at 6.1/9 (SD=2.0). The proportion of parents taking children for regular checkups (56.2%) and replacing toothbrush every three months (53.7%) were the lowest. Information source, occupation, education and perceived necessity of oral care were found to be associated with parents’ knowledge and practices. To conclude, parents had moderate levels of knowledge and practices regarding early dental caries prevention in preschool children. Further studies and interventions should be performed to improve parental knowledge and practices that could enhance the oral health of children.